2018
DOI: 10.1542/peds.2017-4286
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes in Infants With Birth Weight ≤500 g at 3 Years of Age

Abstract: OBJECTIVES: To determine neurodevelopmental outcomes at 3 years of age in children born with a birth weight (BW) of ≤500 g. METHODS: Infants who were born with a BW of ≤500 g from 2003 to 2012 in the Neonatal Research Network of Japan and survived to discharge from the NICU were eligible in this study. The study population consisted of 460 children (56.7% of 811 surviving infants) who were evaluated at 36 to 42 months of age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
0
19
3
Order By: Relevance
“…On the other hand, many unsolved problems remain: NEC, cholestasis, neurodevelopmental impairment, short stature, risk for lifestylerelated diseases, etc. (7,(22)(23)(24)(25)(26). Not only the lung and brain, but also the gastrointestinal tract, liver, and kidney should be restored for the following life.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many unsolved problems remain: NEC, cholestasis, neurodevelopmental impairment, short stature, risk for lifestylerelated diseases, etc. (7,(22)(23)(24)(25)(26). Not only the lung and brain, but also the gastrointestinal tract, liver, and kidney should be restored for the following life.…”
Section: Discussionmentioning
confidence: 99%
“…The brain damage in early life does influence the prognosis of affected children. Hirosuke and his colleagues investigated 3-year-old children's neurodevelopmental outcomes who were born <500 g. Through follow-up visits and data analyses of these survivals, their group made a great discovery that cystic periventricular leukomalacia, a severe category of brain damage in premature infants, was the high risk factor for neurological consequences (adjusted RR:1.40; 95%CI:1.13–1.73; P < 0.01) ( 4 ). So we will first focus on hypoxic-ischemic encephalopathy (HIE), an important component of the brain damage.…”
Section: Circrnas As Potential Biomarkers For Neurological Impairments and Diseasesmentioning
confidence: 99%
“…Generally speaking, the lower the gestational age (GA) and birth weight (BW) are, alone or combined, the higher the morbidity of brain damage is, and so is the mortality ( 3 ). A previous study has shown that premature birth does play an important role ( 4 ). Prematurity may greatly affect the integrity of brain structure and function, as well as health and development of further life ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the development of infants weighing ≤ 300 g has only been mentioned in two articles. Two of the three infants weighing ≤ 300 g included in a Japanese cohort study between 2003 and 2012 were diagnosed with neurodevelopmental impairment at the age of 3 years 10 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%